To research of the feeding of larvae of bloodsucking mosquitoes (Culicidae) of Lower Dagestan - S. S. Gadzhiyeva; A. A. Shaichova (Юг России: экология, развитие)
Intestines of IVth stage larvae of mass species of bloodsucking mosquitoes from the zone affected water reservoir have been studied. As a result it has been established that the main components of their food are algae, detritus, mineral particles and remains of zooplankton.